Lats2-Underexpressing Bone Marrow-Derived Mesenchymal Stem Cells Ameliorate LPS-Induced Acute Lung Injury in Mice - Dong, Liang; Li, Lang (Mediators of Inflammation, 2019)
The pathophysiology of the acute lung injury (ALI) is characterized by the damage of alveolar epithelial cells, which can be repaired by exogenous bone marrow-derived mesenchymal stem cells (BMSCs). However, the migration and differentiation abilities of BMSCs are not sufficient for the purpose, and a new approach that could strengthen the repair effects of BMSCs in ALI still needs to be clarified. We have previously proved that in vitro large tumor suppressor kinase 2- (Lats2-) underexpressing BMSCs may enhance their tissue repair effects in ALI; thus, in the present study, we tried to explore whether Lats2-underexpressing BMSCs could rescue lipopolysaccharide- (LPS-) induced ALI in vivo. BMSCs from C57BL/6 mice transfected with Lats2-interfering lentivirus vector or lentivirus blank controls were transplanted intratracheally into LPS-induced ALI mice. The retention and differentiation of BMSCs in the lung were evaluated by in vivo imaging, immunofluorescence staining, and Western blotting. The lung edema and permeability were assessed by lung wet weight/body weight ratio (LWW/BW) and measurements of proteins in bronchoalveolar lavage fluid (BALF) using ELISA. Acute lung inflammation was measured by the cytokines in the lung homogenate and BALF using RT-qPCR and ELISA, respectively. Lung injury was evaluated by HE staining and lung injury scoring. Pulmonary fibrosis was evaluated by Picrosirius red staining, immunohistochemistry for α-SMA and TGF-β1, and hydroxyproline assay and RT-qPCR for Col1α1 and Col3α1. Lats2-mediated inhibition of the Hippo pathway increased the retention of BMSCs and their differentiation toward type II alveolar epithelial cells in the lung. Furthermore, Lats2-underexpressing BMSCs improved lung edema, permeability of the lung epithelium, and lung inflammation. Finally, Lats2-underexpressing BMSCs alleviated lung injury and early pulmonary fibrosis. Our studies suggest that underexpression of Lats2 could further enhance the repair effects of BMSCs against epithelial impair and the therapeutic potential of BMSCs in ALI mice.